Isolated torrential tricuspid regurgitation and porcelain aorta due to mediastinal radiation therapy. Challenging surgical treatment - Ríos-Ortega, Josías C. (2022)
We present a 64-year-old man diagnosed with Hodgkin's lymphoma at 3 years, who received chemotherapy and several sessions of Mediastinal Radiotherapy (MRT), which caused torrential tricuspid regurgitation (TR), complete heart block (CHB) and porcelain aorta. The patient successfully underwent complex tricuspid repair without cardiac arrest and implantation of an epicardial pacemaker.